Horizontal transmission of disseminated neoplasia in the widespread clam Macoma balthica from the Southern Baltic Sea. Issue 11 (21st April 2022) - Michnowska, Alicja; Hart, Samuel F. M.; Smolarz, Katarzyna; Hallmann, Anna; Metzger, Michael J.
Abstract: Disseminated neoplasia (DN) is one of the most challenging and unrecognised diseases occurring in aquatic fauna. It has been diagnosed in four bivalve species from the Gulf of Gdańsk (Southern Baltic Sea) with the highest frequency in Macoma balthica (formerly Limecola balthica ), reaching up to 94% in some populations. The aetiology of DN in the Baltic Sea has not yet been identified, with earlier studies trying to link its occurrence with environmental pollution. Taking into account recent research providing evidence that DN is horizontally transmitted as clonal cells between individuals in some bivalve species, we aimed to test whether DN is a bivalve transmissible neoplasia (BTN) in the population of M . balthica from the Gulf of Gdańsk highly affected with cancer. We examined mitochondrial cytochrome c oxidase I ( mtCOI ) and elongation factor 1α ( EF1α ) sequences of genomes obtained from haemolymph and tissues of neoplastic and healthy individuals. Sequence analysis resulted in detection of an independent transmissible cancer lineage occurring in four neoplastic clams that is not present in healthy animals. This study describes the first case of BTN in the clam M . balthica (MbaBTN), providing further insights for studies on this disease.